Assessing forest yield and site suitability for Eucalyptus grandis x E. urophylla in coastal Zululand, South Africa, under climate change scenarios - Mfuni, Tiza Ignatius (Stellenbosch : Stellenbosch University, 2022)
Thesis (MFor)--Stellenbosch University, 2022.